2018
DOI: 10.1176/appi.neuropsych.17080173
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Apathy, Health-Related Quality of Life, and Function in Huntington’s Disease

Abstract: Up to 90% of individuals with Huntington's disease (HD)-a progressive, inherited neurodegenerative disorder-experience apathy. Apathy is particularly debilitating because it is marked by a reduction in goal-directed behaviors, including self-care, social interactions, and mobility. The objective of this study was to examine relationships between variables of apathy, functional status, physical function, cognitive function, behavioral status/emotional function, and health-related quality of life. Clinician-rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 38 publications
8
39
0
Order By: Relevance
“…Nine of these studies reported significantly positive correlations with other psychological difficulties including apathy (Bouwens et al, 2015;Pflanz et al, 1991), anxiety (Litvan et al, 1998Nimmagadda et al, 2011;Paulsen et al, 2001), depression (Litvan et al, 1998Nimmagadda et al, 2011;van Duijn et al, 2014), bad temper (Burns et al, 1990) and suicidal ideation and/or behaviour (Anderson et al, 2016;van Duijn et al, 2018). Fritz et al (2018) additionally identified that poorer behavioural scores (a composite score from the PBA-HD short form, covering ten behavioural problems including irritability, although not a specific measure of irritability in itself) were associated with higher apathy scores (large effect size: R 2 = 0.30), in line with research specifically examining irritability as a stand-alone variable.…”
Section: Association With Other Psychological Difficultiessupporting
confidence: 65%
See 3 more Smart Citations
“…Nine of these studies reported significantly positive correlations with other psychological difficulties including apathy (Bouwens et al, 2015;Pflanz et al, 1991), anxiety (Litvan et al, 1998Nimmagadda et al, 2011;Paulsen et al, 2001), depression (Litvan et al, 1998Nimmagadda et al, 2011;van Duijn et al, 2014), bad temper (Burns et al, 1990) and suicidal ideation and/or behaviour (Anderson et al, 2016;van Duijn et al, 2018). Fritz et al (2018) additionally identified that poorer behavioural scores (a composite score from the PBA-HD short form, covering ten behavioural problems including irritability, although not a specific measure of irritability in itself) were associated with higher apathy scores (large effect size: R 2 = 0.30), in line with research specifically examining irritability as a stand-alone variable.…”
Section: Association With Other Psychological Difficultiessupporting
confidence: 65%
“…IRRITABILITY IN HUNTINGTON'S DISEASE 9 (PBA;Craufurd et al, 2001;Gregory et al, 2015;Kingma et al, 2008;Reedeker et al, 2012;Thompson et al, 2002;Thompson et al, 2012;van Duijn et al, 2013;van den Stock et al, 2015), one its Dutch equivalent (NL-PBA; Bouwens et al, 2016), and four the PBA shortform (PBA-s;Fritz et al, 2018;Honrath et al, 2018;Martinez-Horta et al, 2016;Ruiz-Idiago et al, 2017). Three studies used the Irritability Scale (IS; Bouwens et al, 2015;Diago et al, 2018;Reedeker et al, 2012), four used the Snaith Irritability Scale (SIS; Berrios et al, 2001;Klöppel et al, 2010;Maltby et al, 2016) and two the Hospital Anxiety and Depression Scale combined with the SIS (HADS-SIS; Underwood et al, 2016;Vassos et al, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Apathy is a prevalent neuropsychiatric symptom in patients with HD (Camacho, Barker, & Mason, 2018) and has important implications for the patients’ functional capacity of the patient (Hamilton et al, 2003; van Duijn et al, 2014), quality of life (Eddy & Rickards, 2013), employment (Jacobs, Hart & Roos, 2018), and social functioning (Fritz et al, 2018). Indeed, both patients and caregivers rate apathy in the top three most impactful features of the disease (Simpson, Lovecky, Kogan, Vetter, & Yohrling, 2016).…”
mentioning
confidence: 99%